2020
DOI: 10.1094/mpmi-09-19-0271-r
|View full text |Cite
|
Sign up to set email alerts
|

FvSTUA is a Key Regulator of Sporulation, Toxin Synthesis, and Virulence in Fusarium verticillioides

Abstract: Fusarium verticillioides is one of the most important pathogens of maize, causing rot and producing fumonisin mycotoxins during infection. Ingestion of fumonisin-contaminated corn causes underperformance and even fatal toxicity in livestock and is associated with neural tube birth defects, growth stunting in children, and some cancers. StuA, an APSES-class transcription factor, is a major developmental transcriptional regulator in fungi. It has been shown to regulate crucial developmental processes, such as sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 70 publications
2
9
0
Order By: Relevance
“…The APSES transcription factor StuA was previously known as the conserved morphological modifier, playing crucial roles in cellular differentiation, mycelial growth, as well as asexual and sexual development in filamentous fungi [ 21 , 22 ]. Recent studies has suggested that StuA regulates biosynthesis of multiple SM gene clusters in different species [ 21 , 23 ], implying that it might function as a global regulator of SM in fungi. We presumed that StuA might contribute to biosynthesis of terrein in A .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The APSES transcription factor StuA was previously known as the conserved morphological modifier, playing crucial roles in cellular differentiation, mycelial growth, as well as asexual and sexual development in filamentous fungi [ 21 , 22 ]. Recent studies has suggested that StuA regulates biosynthesis of multiple SM gene clusters in different species [ 21 , 23 ], implying that it might function as a global regulator of SM in fungi. We presumed that StuA might contribute to biosynthesis of terrein in A .…”
Section: Resultsmentioning
confidence: 99%
“…The APSES transcription factor StuA was initially found to be a regulator of fungal asexual and sexual development [ 22 ]. Recently, its regulatory role in secondary metabolism has been revealed in several fungi [ 21 , 23 ]. In general, StuA positively regulates the SM gene expression, and its deletion resulted in reduction or even absence of secondary metabolite biosynthesis, such as aflatoxin [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of genes involved in the biosynthesis of epipolythiodioxopiperazine (ETP) gliotoxins is StuA-dependent in A. fumigatus ( 34 ). In Fusarium verticillioides , StuA is required for the production of fumonisin and the expression of genes involved in the biosynthesis of fumonisin and fusarin C ( 46 ). StuA is involved in the production of a mycotoxin (Alternariol) in S. nodorum ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The APSES protein family is a class of transcription factors unique to fungi, including Asm1, Phd1, Sok1, Efg1, and StuA. StuA is involved in various biological functions, including conidiophore formation, spore generation, hyphal growth, secondary metabolism, and pathogenicity [ 11 , 12 , 13 , 14 , 15 ]. Although the StuA protein is highly conserved across a variety of fungi, its potential functions are not consistent.…”
Section: Introductionmentioning
confidence: 99%